PENGARUH TAYANGAN HELL’S KITCHEN DI YOUTUBE TERHADAP PERILAKU MAHASISWA MANAJEMEN TATA BOGA POLITEKNIK PARIWISATA KOTA MEDAN - Sofi Firani; Irene Silviani (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This study discusses about the influence of Hell's Kitchen impressions on Youtube on the Behavior of Management Students of the Polytechnic of Tourism in Medan. This study aims at determining the effectiveness of Hell’s Kitchen shows in influencing behaviors seen from the cognitive, affective and conative aspects of students in the Medan Tourism Polytechnic Management Study Program. The population in this study is as many as 225 students from Tourism Management Study Program Medan Tourism Polytechnic, which were then sampled using the taro yamane formula to 69 respondents. The correlation results see the hell's kitchen show on the behavior obtained a significance value of 0,000 so there is a significant correlation of viewing the hell's kitchen show on the behavior of students of Management Tataboga. Correlation coefficient value of 0.769 means that there is a positive correlation meaning the higher the hell's kitchen shows, the better the behavior will be. The correlation coefficient value is included in the effective category so that seeing hell’s kitchen shows is considered effective in improving the behavior of students in management hopefully. Through the hell's kitchen program students are able to absorb the positive things contained in these shows this shows students have good behavior in absorbing the information obtained.